Osman Bakar’s Thoughts on Tawhid and Implications for Islamic Education in Indonesia - Moh. Hanif Adzhar; Muhammad Zidni Ilman Nafi’a (Dimar Jaya Publishing, 2026)
The dichotomy between religious sciences and general sciences within contemporary Islamic education systems constitutes a pressing epistemological problem that demands resolution. This study aims to analyze Osman Bakar's concept of Tawhid and its implications for the development of Islamic educational thought. A qualitative library research design was employed, using content analysis and hermeneutical approaches to four of Osman Bakar's primary works published between 1994 and 2018, alongside secondary sources comprising journals and conference proceedings from 2020 to 2025, purposively selected for thematic relevance. This study finds that Tawhid, within Osman Bakar's intellectual framework, operates beyond a mere theological doctrine, functioning instead as a fully operational epistemological system that unifies modern scientific knowledge with Islamic spiritual values. The concepts of the hierarchy of knowledge and dual consilience formulated by Bakar are directly translatable to the design of integrative Islamic educational curricula. This study is limited to a textual analysis of a single thinker's primary works and does not include empirical validation of curriculum implementation in actual educational institutions, indicating a need for further field-based research. This study contributes a tawhidic epistemology framework comprising the hierarchy of knowledge and dual consilience as a novel analytical instrument for designing integrative curricula in contemporary Islamic higher education.